2016
DOI: 10.1002/joc.4671
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of heat waves in South Korea and their connection with large‐scale atmospheric circulation patterns

Abstract: This study investigates the interannual variation of heat wave frequency (HWF) in South Korea during the past 42 years and examines its connection with large-scale atmospheric circulation changes. Korean heat waves tend to develop most frequently in late summer during July and August. The leading Empirical Orthogonal Function accounting for 50% of the total variance shows a mono-signed pattern over South Korea, suggesting that the dominant mechanisms responsible for the heat wave are linked in a spatial scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 58 publications
(100 reference statements)
4
95
0
Order By: Relevance
“…Although the magnitude is not strong, negative SST anomalies are commonly found over the tropical eastern Pacific for both cases showing La Niña‐ like structure. Lee and Lee () also obtained the La Niña‐ like pattern in association with the interannual variation of heat wave frequency in Korea. Also, this result is consistent with previous studies that summer air temperature in Korea, Japan, and northeastern China becomes generally warmer than normal during La Niña years (Ueda et al, ; Wang et al, ; Wu et al, ; Yeo et al, ).…”
Section: Dynamical Features Of the Two Types Of Korean Heat Wavementioning
confidence: 87%
“…Although the magnitude is not strong, negative SST anomalies are commonly found over the tropical eastern Pacific for both cases showing La Niña‐ like structure. Lee and Lee () also obtained the La Niña‐ like pattern in association with the interannual variation of heat wave frequency in Korea. Also, this result is consistent with previous studies that summer air temperature in Korea, Japan, and northeastern China becomes generally warmer than normal during La Niña years (Ueda et al, ; Wang et al, ; Wu et al, ; Yeo et al, ).…”
Section: Dynamical Features Of the Two Types Of Korean Heat Wavementioning
confidence: 87%
“…Regardless, the HWN, HWDU, and HWM for both the absolute and relative heat waves demonstrate similar interannual variations with high values in the years 1997, 2010, 2013, etc., and lower values in 1973, 1993, etc. The consistency suggests that these heat wave indices are not independent but rather interrelated even though they represent different aspects of heat waves (Lee & Lee, ). For example, the temporal correlations among the RHWN, RHWDU, and RHWM are all above 0.93.…”
Section: Climatological Characteristics Of Ahws and Rhwsmentioning
confidence: 99%
“…The KMA also suggested that the north–south dipole mode found in the empirical orthogonal function (EOF) analysis for the geopotential height at 500 hPa for the heat wave period in South Korea is similar to the composite difference between the heat‐wave summers (HWS) and the non‐heat‐wave summers (NHWS) in South Korea, emphasizing that the convective activity over the northwestern Pacific Ocean is partly responsible for the heat waves in South Korea. Lee and Lee () also suggested the importance of the convective activity over the northwestern Pacific Ocean based on a regression analysis of the heat wave frequency over South Korea. Thus far, many studies have focused on the roles of tropical forcings in heat waves of East Asia rather than on west–east teleconnections (Nitta, ; Kosaka and Nakamura, ; Wu et al ., ; ).…”
Section: Introductionmentioning
confidence: 99%